(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2021)
The aim of this research is to study and monitor the effectiveness of human resources in the holy province of Karbala, analyzing the research based on the descriptive analytical method, in identifying and addressing the research variables. They are looking for a questionnaire to gather information. You were a sample of the employees of the Internal Control and Audit Division in the province of Karbala, and enable them to choose the way they work in a story (preparation); for the education of holy Karbala, there is no relation to the indication of internal documentation (control environment, risk assessment) and the quality of financial reports of the Directorate General of Research.